Parental attachment, self-esteem and school adolescents in Malaysia - Baharudin, Rozumah; Zulkefly, Nor Sheereen (2011)
The present study aims to determine whether parental attachment influenced the self-esteem and school functioning of Malaysian adolescents. A total of 2062 secondary school students across Malaysia were identified using the Proportional Probability Sampling technique. The participants completed a self-report questionnaire measuring maternal and paternal attachment, self-esteem, school connectedness and trouble in school. A model is presented in which maternal and paternal attachment directly influences self-esteem, school connectedness and trouble in school. Using structural equation modeling, the model was evaluated and minor modifications were done in order to achieve model fit. The model revealed that both parental attachments had direct links with self-esteem and school connectedness of the adolescents. These findings suggest that secure attachment relationships promotes adolescents' positive school functioning behavior by increasing selfesteem and feelings of school connectedness, and decreasing levels of problematic behavior at school. Implication for research elucidating the important role of parental attachment on adolescents' school functioning are further discussed.